Impact of Covid-19 on the Employees’ Mental Health and How it Hampers Creativity and Innovation: A Cross-Cultural Bibliometric Analysis - Rua, Orlando Lima; Getachew, Samrawit (E- Revista de Estudos Interculturais, 2023)
The study aims to carry out a cross-cultural analysis of the impact of Covid-19 on employees’ mental health. The study also analyse ways in which Covid-19 hampers creativity and innovation. The study was guided by four specific objectives which include determining the effect of Covid-19 on the mental health of workers namely to identify factors that contribute to mental health problems among employees during Covid-19; to determine the impact of Covid-19 on the creativity and innovation of workers and to determine the creativities and innovations brought by Covid-19 on workers. The research method used in this study was a systematic review. Studies addressing the impact of covid-19 on employees and creativity and innovation were searched online from PubMed, Scopus, Science Direct, and EMBASE databases. Keywords in combination with key variables were used to search the articles. The review for this study was presented according to the guidelines provided by Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Inclusion and exclusion criteria were used to select the right articles. Inclusion criteria included; articles published in 2019, and articles published in the English language. The findings revealed that the major mental health problems following Covid-19 are stress, fear, depression, anxiety, and sleep disorder. Concerning the second objective, it was found that fear of job loss and lack of social support are the major factors causing mental health problems among employees following the Covid-19 pandemic. The findings in the third objective revealed that creativity enhances resilience, reduce stress, help employees manage challenges brought by Covid-19, help employees accomplish task, control emotions, and enhance productivity. Results on the fourth objective revealed that the major type of creativity identified is teleworking. The major conclusion was that Covid-19 has caused significant mental health problems in employees and enhanced creativity and innovation.